Unleashing Scientific Creativity in Chemistry: Transformative learning activities using Nominal Group Technique - Muhammad, Abu Aswatudali Syawal; Salleh, Salmiza (Environment-Behaviour Proceedings Journal, 2025)
This study aims to examine activities to enhance scientific creativity in secondary school chemistry. Despite its significance, conventional chemistry education frequently stifles creativity due to inflexible, rote memorization strategies. Employing the Nominal Group Technique (NGT), seven experts identified essential activities, including formulating hypotheses, creative experiments, and visualization, as effective strategies. These activities increase scientific creativity dimensions, such as fluency and originality. The findings indicate that all proposed strategies obtained above 70% expert consensus. Future research should investigate the long-term effects with respect to these activities and the integration of digital tools to further enhance scientific creativity in chemistry teaching.